Insulin‐based strategies to prevent hypoglycaemia during and after exercise in adult patients with type 1 diabetes on pump therapy: the DIABRASPORT randomized study. Issue 12 (8th October 2015) - Franc, S.; Daoudi, A.; Pochat, A.; Petit, M.‐H.; Randazzo, C.; Petit, C.; Duclos, M.; Penfornis, A.; Pussard, E.; Not, D.; Heyman, E.; Koukoui, F.; et al.
Abstract : Aims: To validate strategies to prevent exercise‐induced hypoglycaemia via insulin‐dose adjustment in adult patients with type 1 diabetes (T1D) on pump therapy. Methods: A total of 20 patients randomly performed four 30‐min late post‐lunch (3 h after lunch) exercise sessions and a rest session: two moderate sessions [50% maximum oxygen consumption (VO2 max)] with 50 or 80% basal rate (BR) reduction during exercise + 2 h and two intense sessions (75% VO2 max) with 80% BR reduction or with their pump stopped. Two additional early post‐lunch sessions (90 min after lunch) were analysed to compare hypoglycaemia incidence for BR reduction versus bolus reduction. Results: In all, 100 late post‐lunch sessions were analysed. Regardless of exercise type and BR reduction, no more hypoglycaemic events occurred in the period until the next morning than occurred after the rest sessions. In the afternoon, no more hypoglycaemic events occurred with 80% BR reduction/moderate exercise or with pump discontinuation/intense exercise than for the rest session, whereas more hypoglycaemic events occurred with 50% BR reduction/moderate exercise and 80% BR reduction/intense exercise. After early post‐lunch exercise (n = 37), a trend towards fewer hypoglycaemic episodes was observed with bolus reduction versus BR reduction (p = 0.07). Mean blood glucose fell by ∼3.3 mmol/l after 30 min of exercise, irrespective of dose reduction, remaining stable until the next morning with no rebound hyperglycaemia. Conclusion: In adults with T1D, to limit the hypoglycaemic risk associated with 30 min of exercise 3 h after lunch, without carbohydrate supplements, the best options seem to be to reduce BR by 80% or to stop the pump for moderate or intense exercise, or for moderate exercise 90 min after lunch, to reduce the prandial bolus rather than the BR.